Variability in the relationship between serum creatinine and creatinine clearance in hypertensives and normotensives with normal renal function (2000)
Variabilities exist in the relationship between serum creatinine (Se-C) and creatinine clearance (CCr) due to the influences of age, muscle mass and gender on creatinine production. We studied this variability in a group of hypertensives (n = 62, 30 male, age 44 ± 7 years) and normotensives (n = 90, 47 male, age 42 ± 1 0 years) with normal renal function (Se-C< 0.01) and females (84 ± 19mL/min Vs 96 ± 19mL/min, P < 0.01). Crude CCr was significantly higher in men than women (.P < 0.05) in the whole group but not significantly in the normotensive or hypertensive subgroups. After adjustment, the differences diminished and became insignificant in the whole group. Some subgroups had identical mean Se-C values but different adjusted CCr. A particular Se-C value did not always indicate a particular CCr. Adjustment of CCr to 1.73 m2 BSA reduced the variability between Se-C and CCr and the difference between the genders. CCr showed significant difference in renal function between subgroups where Se-C did not.